Osteonecrosis of the Femoral Head : A Clinical Casebook - Sierra, Rafael J. (Springer International Publishing : Imprint: Springer, 2017)
Comprised exclusively of clinical cases involving osteonecrosis of the femoral head (ONFH), this concise, practical casebook will provide orthopedic surgeons with the best real-world strategies to properly diagnose and treat both pre- and post-collapse conditions. Each chapter is a case that opens with a unique clinical presentation, followed by a description of the diagnosis, assessment and management techniques used to treat it, as well as the case outcome and clinical pearls and pitfalls. Part I discusses pre-collapse treatments aimed at the early stages of ONFH, including the use of bisphosphonates, stem cell therapy and minimally invasive core decompression. Chapters presenting post-collapse treatments aimed at preserving the femoral head comprise part II, including non-vascularized bone grafting, osteochondral transfer and transtrochanteric osteotomy. Cases covering post-collapse total hip arthroplasty (THA) and common complications round out the presentation. Pragmatic and reader-friendly, Osteonecrosis of the Femoral Head: A Clinical Casebook will be an excellent resource for orthopedic surgeons, residents and fellows treating hip pain.
Keywords: Medicine.; Rheumatology.; Orthopedics.; Sports medicine.; elektronické knihy; electronic books